2014
DOI: 10.3855/jidc.4810
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical pulmonary pathogenic infection in camels slaughtered in Cairo, Egypt

Abstract: Introduction: Camels migrate between the open boundaries of Sudan and Egypt either for grazing or for slaughtering. Bad hygiene and stress is often related to pulmonary diseases in camels. This study investigated whether camels slaughtered in Cairo carried pulmonary infections. Methodology: Five hundred lung tissues of slaughtered camels were examined and 100 samples suspected for pulmonary infection were subjected to microbial identification and histopathology. Results: A total of 70 lung tissues revealed 97 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
4
15
2
Order By: Relevance
“…The characters of the isolated colonies and their biochemical identification tests were in agreement with those previously reported [20]. However, in previous reports, several microorganisms including Pasteurella hemolytica were also recovered from lung of camels with pneumonic pasteurellosis [5], suggesting that other contributing factor may influence the severity of the disease.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The characters of the isolated colonies and their biochemical identification tests were in agreement with those previously reported [20]. However, in previous reports, several microorganisms including Pasteurella hemolytica were also recovered from lung of camels with pneumonic pasteurellosis [5], suggesting that other contributing factor may influence the severity of the disease.…”
Section: Resultssupporting
confidence: 81%
“…Respiratory airway diseases are encountered as an emerging health hazards to camel population worldwide due to significant mortalities and cost of treatment and vaccination [3]. The definite etiology of most respiratory tract diseases of camels has not yet been fully determined [4,5]. Moreover, several important predisposing factors as sudden climatic changes, poor management practices, exposure to various diseases, frequent travelling and poor nutrition may influence the occurrence of such diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that a wide variety of bacterial species colonize the respiratory passageways of camels in the study area. This is supported by several researchers who previously demonstrated diverse bacterial species from various regions of the camel respiratory tract: nasal tracts, tonsil, trachea and lungs (Ismail et al 2014;Wareth et al 2014), and normal and pneumonic lungs (Wareth et al 2014;Ahmed and Musa 2015).…”
Section: Discussionsupporting
confidence: 53%
“…Streptococcus species have been isolated from clinically healthy camels although they were not definitely identified and characterized. Besides, Streptococcus species have been isolated from active respiratory disease of camels (Wareth et al 2014). But there is no data on the isolation of S. equi subsp.…”
Section: Introductionmentioning
confidence: 99%
“…However, the normal flora in apparently healthy camels can be altered by several factors such as bad sanitation, stress due to transportation, sudden change in feed, low herd health status, and immunosuppression. This could end up lowering the resistance of the respiratory system to infection [36]; thus, the existing nasal organisms could cause infections in the nasal cavity or end up finding their way down the system and eventually cause pathology in the lower respiratory system of the respective camels [37]. …”
Section: Discussionmentioning
confidence: 99%